CRESCIMENTO DO HÍBRIDO UROGRANDIS SUBMETIDO A DESRAMA ARTIFICIAL EM SISTEMA SILVIPASTORIL - RODRIGUES, Carolina Garcia; VILELA, Luiz Renato Santos; DE ANGELES, Rafael Ruffato; SOUZA, Vitória Cristina di Matheus e; MARQUES FILHO, Wolff Camargo; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2022)
-